2002
DOI: 10.1073/pnas.192365599
|View full text |Cite
|
Sign up to set email alerts
|

Floral responses to photoperiod are correlated with the timing of rhythmic expression relative to dawn and dusk inArabidopsis

Abstract: Daylength, or photoperiod, is perceived as a seasonal signal for the control of flowering of many plants. The measurement of daylength is thought to be mediated through the interaction of phototransduction pathways with a circadian rhythm, so that flowering is induced (in long-day plants) or repressed (in short-day plants) when light coincides with a sensitive phase of the circadian cycle. To test this hypothesis in the facultative long-day plant, Arabidopsis thaliana, we used varying, non-24-hr light͞dark cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 32 publications
(31 reference statements)
2
82
0
1
Order By: Relevance
“…When the day-night cycle is shortened to 21 h and thus matched to the endogenous period in toc1 mutants, the CO pattern no longer differs from that in wild type and the short-day early flowering phenotype of toc1 is suppressed (Strayer et al 2000;Yanovsky and Kay 2002). Additional, more sophisticated manipulations of length and structure of the light/dark cycle, similar to what had been used in the early days of studying the circadian clock (Nanda and Hamner 1958;Pittendrigh 1960), confirmed that bringing peak levels of CO mRNA into the light phase promotes flowering of wild-type plants under short photoperiods (Roden et al 2002).…”
Section: Molecular Basis Of the External Coincidence Modelmentioning
confidence: 75%
“…When the day-night cycle is shortened to 21 h and thus matched to the endogenous period in toc1 mutants, the CO pattern no longer differs from that in wild type and the short-day early flowering phenotype of toc1 is suppressed (Strayer et al 2000;Yanovsky and Kay 2002). Additional, more sophisticated manipulations of length and structure of the light/dark cycle, similar to what had been used in the early days of studying the circadian clock (Nanda and Hamner 1958;Pittendrigh 1960), confirmed that bringing peak levels of CO mRNA into the light phase promotes flowering of wild-type plants under short photoperiods (Roden et al 2002).…”
Section: Molecular Basis Of the External Coincidence Modelmentioning
confidence: 75%
“…The double mutant is almost day neutral and has an early phase of circadian gene expression during day-night cycles (Mizoguchi et al 2002). It has been proposed that this circadian phenotype affects the phase of CO expression during short days, thereby leading to early flowering (Mizoguchi et al 2002;Roden et al 2002;Yanovsky and Kay 2002). Interestingly, the circadian and flowering-time phenotypes of srr1 mutants are very similar to those of cca1, lhy, and toc1 loss-of-function alleles, clearly suggesting a role for SRR1 in the clock (Figs.…”
Section: Srr1 Is Required For Normal Circadian Oscillator Functionmentioning
confidence: 99%
“…In the flowering plant Arabidopsis thaliana, the circadian clock phases the peak mRNA abundance of many genes to distinct times of day (3). Furthermore, the phase angle of specific circadian rhythms with the environmental light-dark (LD) cycle controls seasonal behavior such as flowering (4)(5)(6).…”
mentioning
confidence: 99%